Pelatihan dan Pendampingan Guru SMP dalam Penyusunan LKPD IPA Terpadu Terintegrasi Kearifan Lokal Aceh - Nur Azizah Lubis; Coryna Oktaviani; Mentari Darma Putri; Aldeva Ilhami (Peneliti.net, 2022)
This community service aims to improve the knowledge, understanding and skills of junior high school science teachers in Langsa City in designing learning tools in the form of Student Worksheets (LKPD) integrated with Acehnese local wisdom. The activities were carried out on July 29 and August 5, 2022 at SMP N 5 Langsa City. The targets in this activities were junior high school science teachers who were members of the Langsa City Science MGMP, totaling 27 people. This community service activity consisted of three stages, namely the preliminary stage, implementation and evaluation and reflection. In the preliminary stage, the community service team discussed with partners regarding the problems experienced by partners and jointly designed solution plans. The implementation phase was divided into two main activities, namely training and mentoring activities. The training activities were carried out face-to-face and then continued with the teachers who were accompanied by the community service team to design and compile LKPD according to the correct writing systematics. The evaluation and reflection stages were carried out to find out the shortcomings of the LKPD made. Participants were given a questionnaire to explore information related to their level of understanding after attending the training and mentoring. The training and mentoring activities were carried out well, received positive responses from partners and there was an increase in teacher understanding of 81.5% in compiling Student Worksheets (LKPD) integrated with Acehnese local wisdom.